Handbook of Metalloproteins 2004
DOI: 10.1002/0470028637.met026
|View full text |Cite
|
Sign up to set email alerts
|

Neprilysin

Abstract: Neprilysin (NEP), a thermolysin‐like zinc metalloendopeptidase, is the major enzyme involved in the metabolic inactivation of a number of bioactive peptides including the enkephalins, substance P, endothelin, bradykinin, and the atrial natriuretic factor. NEP is an integral plasma membrane endopeptidase of the M13 family of zinc peptidases. Other related mammalian NEP‐like enzymes include the endothelin‐converting enzymes (ECE‐1 and ECE‐2), KELL and PEX. A number of novel mammalian homologues of NEP have also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Current knowledge of the NEP binding pocket centers on the amino acid residues surrounding its zinc(II) ion (Zn 2+ ) cofactor. X-ray crystallographic studies of seven different inhibitor-bound NEP complexes indicate that the Zn 2+ is coordinated to a bound ligand by two conserved, consensus sequences: 583 HExxH 587 and 646 ExxxD 650 . In addition, E584 appears to be involved in a complex hydrogen (H) bonding network with N542 and A543 of a consensus NAFY motif as well as R717, H711, and other residues around the NEP binding pocket . The crystal structures verified prior efforts to group NEP residues into binding subsites and label them with Schechter and Berger notation, which uses the letter S and a number to represent the relative position of pocket residues to ligand atoms that are labeled correspondingly using the letter P. The NEP residues Y545 and E584 of the S1 site interact with P1 atoms located on the amino terminal side of a substrate’s carbonyl-amide scissile bond.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Current knowledge of the NEP binding pocket centers on the amino acid residues surrounding its zinc(II) ion (Zn 2+ ) cofactor. X-ray crystallographic studies of seven different inhibitor-bound NEP complexes indicate that the Zn 2+ is coordinated to a bound ligand by two conserved, consensus sequences: 583 HExxH 587 and 646 ExxxD 650 . In addition, E584 appears to be involved in a complex hydrogen (H) bonding network with N542 and A543 of a consensus NAFY motif as well as R717, H711, and other residues around the NEP binding pocket . The crystal structures verified prior efforts to group NEP residues into binding subsites and label them with Schechter and Berger notation, which uses the letter S and a number to represent the relative position of pocket residues to ligand atoms that are labeled correspondingly using the letter P. The NEP residues Y545 and E584 of the S1 site interact with P1 atoms located on the amino terminal side of a substrate’s carbonyl-amide scissile bond.…”
Section: Introductionmentioning
confidence: 57%
“…Over the 500 ps duration of the three BIR1 MD simulations, the average model distances of the Zn 2+ from atoms in the NEP residues H583 (2.14 Å), H587 (1.94 Å), E646 (1.73 Å), and a BIR1 phosphinic oxygen (1.75 Å) were relatively comparable to the distances of the crystal structure atoms (2.04, 2.12, 1.98, and 1.94 Å respectively) . The NEP model with S- thiorphan (Figure B) also compared favorably to previous NEP models based on a crystal structure for the NEP homologue Thermolysin (PDB: ). , The bacterial enzyme Thermolysin contains analogous pocket structures that have been used by other groups to model NEP binding interactions with thiorphan. ,,, The S -thiorphan model and crystal structure both indicate a dual hydrogen bonding interaction with N542 in the NEP S2′ site, the inhibitor phenyl group near S1′ residues V580, W693, and R717 as well as sulfhydryl coordination with Zn 2+ and H711. Parallels with experimental observations were preserved in MD simulations, including the average model distances of the Zn 2+ to NEP H583 (2.18 Å), H587 (2.20 Å), E646 (1.80 Å), and the ligand sulfur atom (2.04 Å) compared to crystal structure distances (1.88, 1.94, 1.87, and 2.12 Å, respectively). , …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, the side chain of Glu-451 (of the unbound protein) is appropriately positioned to activate this water molecule for the nucleophilic attack onto the amide bond. As in the proposed mechanisms of thermolysin (33) and neprilysin (34), the hydrogen bond between His-568 and the carbonyl group of Val-2 (Fig. 2B) likely provides additional stabilization of the tetrahedral intermediate (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 84%
“…This is in agreement with the increased hydrophobicity of the S1 sub-site in ECE-1 and the minor stabilizing role of this sub-site in human NEP, for which both compounds show similar IC 50 values. [42][43][44][45] Extensive studies have shown that there is a clear preference for P1′ residues with large hydrophobic side chains, indicating that the specificity of ECE-1 is essentially ensured by this sub-site. 39 The P1′ residue of phosphoramidon and its interaction with the S1′ sub-site is shown in Fig.…”
Section: Phosphoramidon Sub-site Recognition and Specificitymentioning
confidence: 99%